Insertion of Argentine firms in global value chains not oriented to the mass market: The cases of high-end footwear and the Basso group - Andrea González; Juan Carlos Hallak; Peter Schott; Tatiana Soria Genta (Inter-American Development Bank (IDB), 2012)
This paper describes experiences of international insertion of Argentine producers of manufactured goods not oriented to the mass market. Based on these experiences, we develop a typology of potential alternatives of international insertion for this type of goods centered on the role of local agents in design activities. Our analysis follows the global value chain (GVC) approach and emphasizes the links between local producers and buyers in developed countries. First, we analyze experiences of international insertion of producers and marketers of high end footwear. These cases involve high quality products that are intensive in original design. Second, we analyze various forms of international insertion of a single producer of valves for combustion engines, which primarily involve customized products. Despite the differences between these two industries, we find notable similarities in the forms of insertion they both present and in the knowledge requirements they impose on local producers.
hdl:11319/4253
Keywords: F14; F23; 330; Global Supply Chains; International Fragmentation of Production; Suppliers